The effects of planktivorous fish on phytoplankton community structure. - Proulx, Marc. (University of Ottawa (Canada), 1993)
The response of phytoplankton to nutrient loading and planktivorous fish additions was investigated in large experimental enclosures installed in lac Croche at the Station de Biologie des Laurentides de l'Universite de Montreal. During the summer period (July and August), phytoplankton biomass significantly increased with fertilization and the presence of fish in the deep, thermally stratified, enclosures. The presence of fish increased algal biomass, particularly under the fertilized conditions. In the shallow, thermally mixed enclosures, total phytoplankton biomass was significantly affected by fertilization but not by the presence of fish. The taxonomic composition at both the species and the division levels differed in all treatments. In the deep stratified enclosures, both the addition of nutrient (p .001) and fish (p =.003) favored a large increase in Chlorophyta biomass which was composed of 1 or 2 species. Pyrrhophytes increased slightly with the presence of fish. In the shallow enclosures, nutrient additions significantly affected the division composition of total algal biomass, whereas presence of fish did not. The presence of planktivorous fish influenced phytoplankton community structure by modulating total algal biomass, the distribution of biomass according to size classes and the overall taxonomic composition. The impacts of fish were more numerous in the deep than in the shallow enclosures. Thermal stratification may thus be an important factor influencing the impact of planktivorous fish on phytoplankton. (Abstract shortened by UMI.)
Keywords: Biology, Ecology.